Digital Disobedience and the Limits of Persuasion: Social Media Activism in Hong Kong's 2014 Umbrella Movement. (February 2019) - Agur, Colin; Frisch, Nicholas
This article probes the catalytic features of social media in civic participation and mass civil disobedience in Hong Kong's 2014 protests, and conceptualizes digital activism in terms of mobilization, organization, and persuasion. It makes use of in-depth interviews, in English, Mandarin, and Cantonese, with 40 of the leading users of social media during the protests. These included, first and foremost, student activists, as well as opposition figures and journalists who reported on the protests. The article finds that the velocity and scale of social media have strengthened protesters' ability to mobilize and organize, on the Internet and in the streets. Yet, these advantages have not carried over into persuasion of previously uncommitted individuals. Protesters encountered two main obstacles to persuasion via social media: the multitude of messages enabled by social media and the age segmentation of media. As a result, the movement's social media efforts generated new attention and created digital space for activism, but did not persuade a durable majority of Hongkongers of the movement's legitimacy. The Umbrella Movement may not have persuaded Hongkongers that their movement and tactics were valid or wise, but the existence of social media allowed protest leaders to document their motivations and conduct, and blunt less flattering narratives in legacy media.